Efficacy of Terbinafine 1% cream versus Clotrimazole 1% cream in the treatment of Pityriasis Versicolor - SM Rezvani, (Babol University of Medical Sciences, 2006)
BACKGROUND AND OBJECTIVE: Terbinfine a member of allylamines group is a new class of antimycotic agents that blocks sterol biosynthesis in the fungi through inhibition of sequlene epoxidase and with consequent sequalene accumulation due to a primarily fungicidal process. Terbinafine is very effective on various fungi as an oral and topical antifungal agent. The aim of this study was to compare the antifungal efficacy of terbinafine 1% cream with clotrimazole 1% in patients with pityriasis versicolor.METHODS: This clinical trial study was performed on 50 patients (30 males and 20 females) with mean age of 20 years (aged between 15-55 years) who randomly treated with terbinafine and clotrimazole for 4 weeks. The efficacy of drug and improving process evaluated mycologically and clinically before starting the study and at the end of each week. A patient was considered mycologically cured when direct microscopy was negative and clinically cured when all clinical parameters were considered negative.FINDINGS: Negativizations of all clinical parameters were observed within 2 weeks in 60% of terbinofine and 35% clotrimazole recipients. At the end of four weeks, disappear of lesions were seen in 90% and 80%, respectively (p0.05). Both drug eruptions and intolerance in two treated groups were similar.CONCLUSION: Although the efficacy of the both drugs is similar, but considering the expense of therapy, clotrimazole is preferred regimen for therapy of tinea versicolor.